Development of a mobile application for low light level imaging - Tin Htet Htet Naing (Nanyang Technological University, 2023)
Low light photography is not only nighttime photography but also the indoors photography in the middle of the day. Low light portraits in the indoor, landscape shoots at night, fog and mist at night, city night lights photography and night sky photography are parts of the low light photography. There is a technical complexity challenge in night photography due to limited light and different types of low light photography need to have different in-depth understanding of the different equipment to achieve. Using a tripod to stabilize, Increasing ISO and using slower shutter speed for longer exposure are some of the methods to get better low light images. Moreover, photographing in low light situations needs to follow with post-processing which is used for improving the signal-to-noise ratio in imaging for accomplishing a perfect image. Stacking images is one of the post-processing methods to reduce the digital noise and it is used in astrophotography and others which are not suitable to increase the exposure time in a single shot. It will produce a finalized stacked image by aligning and averaging pixels. The details of low light imaging techniques are researched and applied to accomplish this project. In this project, the mobile application of image processing for low light photography will be created for the user. The user will be able to get a stacked image with one single click and it will be an easy-to-use way to use. Capturing and image processing will be done in a short time with a single device. Besides, the application allows the user to choose multiple images to process the final image and it can be checked on spot.